Control de inventario de la constructora Arregui Dávila S. A. ADSA. - Alvarado Sánchez, Kevin Hilario (2022)
The present investigation is oriented to analyze the inventory control in the company Constructora Arregui Dávila S.A ADSA of the Babahoyo Canton, which is dedicated to the cultivation of bananas and plantains. Since inventory control is of utmost importance for the company's activities. In companies, the item of inventory has become a constant problem in terms of planning and control because it is directly related to its cost, since these tangible goods are the ones that provide great value so that economic income is generated for the company. In addition, this case study is framed under the Financial, Administrative, Tax, Audit and Control Management research line, and the Audit and Control research sub-line. In turn, for the present case study, the type of descriptive research was used, which allowed knowing the reasons and circumstances that generated the problems and the current situation that the company is going through. And the qualitative and quantitative research approaches were used, the qualitative approach provided data collection without numerical measurement that allowed obtaining an overview of the research, instead the quantitative approach was reduced for data collection, based on measurement numerical and analysis of such data.